2021
DOI: 10.14814/phy2.15100
|View full text |Cite
|
Sign up to set email alerts
|

Microbial disruption in the gut promotes cerebral endothelial dysfunction

Abstract: Cerebrovascular disease is a group of conditions characterized by disorders of the cerebral vessels. Endothelial dysfunction renders the vasculature at risk of impaired blood flow and increases the potential of developing cerebrovascular disease. The gut microbiota has been recently identified as a possible risk factor of cerebrovascular disease. However, a direct link between gut microbiota and cerebral vascular function has not been established. Therefore, the aim of this study was to determine the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…However, according to Shade and colleagues 16 diversity is neither good nor bad, it simply "is", and its deviations can be utilized in clinical settings. In terms of CVS, there is evidence that gut microbiome alterations including bacterial sub-population diversity might result in endothelial dysfunction, which in turn is strongly linked to vasospasm 17 . Also, bacterial diversity alters levels of plasma trimethylamine N-oxide (TMAO) of bacterial origin 18 .…”
Section: Mca Vasospasm Is Linked To Reduced Microbial Diversitymentioning
confidence: 99%
“…However, according to Shade and colleagues 16 diversity is neither good nor bad, it simply "is", and its deviations can be utilized in clinical settings. In terms of CVS, there is evidence that gut microbiome alterations including bacterial sub-population diversity might result in endothelial dysfunction, which in turn is strongly linked to vasospasm 17 . Also, bacterial diversity alters levels of plasma trimethylamine N-oxide (TMAO) of bacterial origin 18 .…”
Section: Mca Vasospasm Is Linked To Reduced Microbial Diversitymentioning
confidence: 99%
“…Observational case–control study design prevailed (see Table 1 and Supplementary material 1 ). Although two studies (Rustia et al, 2021 ; Xiao et al, 2022 ) addressed cerebral ischemic complications due to endothelial dysfunction or cerebral hypoperfusion in subjects with altered microbiota, they were not in the setting of aneurysmal rupture. Therefore, they were not included in the systematic review but were discussed as a pathophysiological rationale for conducting a research study on associations between cerebral vasospasm and intestinal microbiome (see Cerebral vasospasm and delayed cerebral ischemia Section).…”
Section: Gut–brain Axis Alterations Might Confer Risk Toward Cerebral...mentioning
confidence: 99%
“…It has been shown that alteration of gut microbiome might lead to endothelial dysfunction which is one of the core mechanisms of vasospasm. Rustia et al ( 2021 ) presented an experimental animal study showing that antibiotic treatment disrupting gut microbiota leads to endothelial dysfunction by the reduction of phosphorylated endothelial nitric oxide synthase (eNOS-p) to total eNOS ratio (a surrogate marker to eNOS activity). The gut dysbiosis obtained via a 3-week antibiotic regimen also produced increased spontaneous tone of the endothelium, decreased response to NG-Nitro-l-Arginine Methyl Ester (L-NAME) which is a non-selective nitric oxide synthase, and diminished ATP-mediated luminal dilation.…”
Section: Diagnostic and Therapeutic Potentialmentioning
confidence: 99%
“…Moreover, exposure to GLP-1 increases energy expenditure in muscle at least in part through the upregulation of fat oxidation [ 56 ]. Recently, disruption of the gut microbiota has been associated with a reduction of eNOS activity in cerebral ECs highlighting the potential of the microbiota as a target to reverse endothelial dysfunction [ 57 ]. There is evidence that GLP-1 may play a role in the function of the intestinal epithelium, correlating these effects with changes in gut microbiota.…”
Section: Glp-1ra Effect On Endothelial Metabolism: a New Avenue To Ex...mentioning
confidence: 99%